2013
DOI: 10.4314/ijbcs.v7i1.30
|View full text |Cite
|
Sign up to set email alerts
|

Opportunités et contraintes agroforestières de <i>Ricinodendron heudelotii</i> au Cameroun

Abstract: Ricinodendron heudelotii est une essence endémique des forêts tropicales humides d'Afrique, très prisée pour ses graines comestibles. Sa régénération naturelle reste difficile à cause principalement de la dormance tégumentaire de ses graines. Elle possède de nombreuses vertus ethnobotaniques et d'opportunités agroforestières pour les peuples des forêts du bassin du Congo. Au nombre de ces vertus, on cite des propriétés médicinales, agroalimentaires, agronomiques, écologiques et industrielles. Des programmes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…These ndings were supported by several other studies which showed that germination of species is subject to various constraints, including the germinability which varies according to the technique (or pre-treatment) applied. These results showed that integumentary dormancy hinders the germination of B. aegyptiaca and R. heudelotii seeds and corroborate those on B. aegyptiaca (Boubacar et al 2018;Kouyaté et al 2015) and R. heudelotii (Djeugap et al 2013;Kouame et al 2012;Moussa et al 2020) that reported an onset of germination varying from day-6 to day-14. This con rms that seed dormancy of these species is physical and scari cation of the seed coat is necessary to promote seed imbibition and germination.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These ndings were supported by several other studies which showed that germination of species is subject to various constraints, including the germinability which varies according to the technique (or pre-treatment) applied. These results showed that integumentary dormancy hinders the germination of B. aegyptiaca and R. heudelotii seeds and corroborate those on B. aegyptiaca (Boubacar et al 2018;Kouyaté et al 2015) and R. heudelotii (Djeugap et al 2013;Kouame et al 2012;Moussa et al 2020) that reported an onset of germination varying from day-6 to day-14. This con rms that seed dormancy of these species is physical and scari cation of the seed coat is necessary to promote seed imbibition and germination.…”
Section: Discussionsupporting
confidence: 76%
“…This manual scari cation (T2) consists to physically open (slightly damaged) the seed coat to allow moisture and air in. Both pre-treatment techniques were identi ed as adequate with high germination rates: 50-90% for B. aegyptiaca (Boubacar et al 2018;Kouyaté et al 2015) and 63-88% for R. heudelotii (Djeugap et al 2013;Kouame et al 2012). Viable seeds (i.e., able to germinate when conditions are right, provided that any dormancy has been broken) were selected from a viability test following the method of (Assogbadjo et al 2010).…”
Section: Experimental Design and Data Collectionmentioning
confidence: 99%
“…The low germination rate of R. heudelotii seeds limits its widespread ability. Applied mechanical scarification (Djeugap et al, 2014;Marie-Thérèse et al, 2012) has increased the germination rate. In the present study, lime scarification, coupled with the soaking of seeds into the water was examined on several geographically distinct provenances to identify the best ones to be used in reforestation and ex-situ introduction programs.…”
Section: Discussionmentioning
confidence: 99%
“…However, seeds of this species do not germinate without prior treatment (Mapongmetsem et al, 1999) due to their tegumentary dormancy (Djeugap et al, 2014). In view of its multiple uses, the lifting of seed inhibition in the germination process has been discussed by several authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation